2021
DOI: 10.5534/wjmh.200115
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Semen Processing on Sperm Function: Differences between Swim-Up and Density Gradient Centrifugation

Abstract: Andrology research has evolved notoriously in the latest years, particularly since male factor contribution to couple infertility has been undoubtedly demonstrated. However, sperm function investigations results are sometimes contradictory, probably as a result of the use of different sperm processing techniques. In this work, we underwent a systematic functional comparison of human sperm samples simultaneously processed by swim-up and density gradient centrifugation, which are the preferred sperm processing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
(31 reference statements)
0
8
0
2
Order By: Relevance
“…This is consistent with a previous report by Van Der Zwalmen [ 29 ]. This finding may be explained by DGC’s selection of sperm with good capacitation and acrosome reaction abilities, which are key indicators of the ability of sperm to fertilize an egg [ 8 , 28 , 31 ]. That is, the DGC selects morphologically normal sperm cells, especially sperm with normal heads, based on their specific density.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with a previous report by Van Der Zwalmen [ 29 ]. This finding may be explained by DGC’s selection of sperm with good capacitation and acrosome reaction abilities, which are key indicators of the ability of sperm to fertilize an egg [ 8 , 28 , 31 ]. That is, the DGC selects morphologically normal sperm cells, especially sperm with normal heads, based on their specific density.…”
Section: Discussionmentioning
confidence: 99%
“…That is, the DGC selects morphologically normal sperm cells, especially sperm with normal heads, based on their specific density. The sperm recovered by DGC thus have better acrosome function, capacitation, and sperm hyperactivation than those recovered by SU [ 8 , 28 , 31 ]. The resulting higher fertilization rate following DGC increases the number of available embryos and results in a better cLBR relative to SU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the latter is less efficient than SU in selecting sperm cells with intact DNA [ 66 ]. While these theories have been reinforced by more recent studies [ 67 ], in contrast, other authors have shown that DGC is better than SU to select a higher percentage of capacitated sperm [ 68 ] with hyper-activated motion even in cases of subfertility [ 69 ]. Other scientists suggest that neither method provides a cell population with acceptable levels of intact DNA.…”
Section: Classic Methodsmentioning
confidence: 99%
“…An important issue in the advancement of andrology is a lack of consistency between research groups, and indeed clinics, in sperm handling techniques and in culture media composition. This may, in part, explain some of the uncertainty and conflicting literature in the field (Hernández-Silva, et al 2020). For example, recent work elucidating the mechanistic role of albumin in activating the proton channel hHv1 and capacitation of human sperm (Zhao, et al 2021) highlights the importance of sufficient levels of albumin in sperm culture media to fully support capacitation.…”
Section: High Throughput Phenotypic Screeningmentioning
confidence: 99%